Women’s neuroplasticity during gestation, childbirth and postpartum - Paternina-Die, María; Martínez-García, Magdalena; Martín de Blas, Daniel; Noguero, Inés; Servin-Barthet, Camila; Pretus, Clara; Soler, Anna; López-Montoya, Gonzalo; Desco, Manuel; Carmona, Susana (Nature Neuroscience, 2024)
Pregnancy is a unique neuroplastic period in adult life. This longitudinal study tracked brain cortical changes during the peripartum period and explored how the type of childbirth affects these changes. We collected neuroanatomic, obstetric and neuropsychological data from 110 first-time mothers during late pregnancy and early postpartum, as well as from 34 nulliparous women evaluated at similar time points. During late pregnancy, mothers showed lower cortical volume than controls across all functional networks. These cortical differences attenuated in the early postpartum session. Default mode and frontoparietal networks showed below-expected volume increases during peripartum, suggesting that their reductions may persist longer. Results also pointed to different cortical trajectories in mothers who delivered by scheduled C-section. The main findings were replicated in an independent sample of 29 mothers and 24 nulliparous women. These data suggest a dynamic trajectory of cortical decreases during pregnancy that attenuates in the postpartum period, at a different rate depending on the brain network and childbirth type.
Keywords: women; neuroplasticity; gestation; childbirth; postpartum; Scopus